Modeling of hydrogen liquefaction using magnetocaloric cycles with permanent magnets. (November 2020) - Feng, Tianshi; Chen, Renkun; Ihnfeldt, Robin V.
Highlights: Modeled hydrogen liquefication from 80 to 20 K in a multi-stage AMR system using permanent magnets with 1-Tesla field. Achieved over 60% of Carnot COP with the multistage design with optimized operation conditions. Compared two types of 1D AMR models: steady state and time-dependent models. Abstract: Hydrogen (H2 ) is promising alternative to replace fossil fuels, but its transport and storage has been challenging. As H2 fuel cell vehicles are gaining traction, the infrastructure for storing large amounts of liquid H2 is needed. However, liquid H2 would suffer from boil-off loss, and traditional vapor compression refrigeration systems would not be able to economically recover the lost H2 due to the low efficiencies at cryogenic temperature. Magnetocaloric (MC) refrigeration systems could possess much higher coefficient of performance (COP) at cryogenic temperature compared to the vapor compression ones. Previous work on cryogenic MC systems, however, have only focused on large scale applications which use superconducting magnets to provide a large magnetic field but are prohibitively expensive to operate for small scale applications, such as that of a H2 refilling station. In this work, we model the performance of a MC refrigeration cycle using 1-Tesla permanent magnets for H2 liquefaction, with the objective of cooling H2 from 80 K (using liquid nitrogen as the heat sink) to 20 K (boiling point of hydrogen). We evaluate main performance metrics including the total work input to the refrigeration system, COP, total MCM mass in the system, and total volume of the permanent magnets, etc. Our modeling results indicate that such a permanent magnet-based MC cooling system is feasible for small-scale H2 liquefaction, with projected COP values significantly higher than those of vapor compression systems. This work provides design guidelines for future experimental efforts on permanent magnet MC cooling systems for cryogenic cooling.